Peran Pondok Pesantren dalam Melestarikan Al-Barzanji di Pondok Pesantren Irsyadul Islamiyah Tanjung Medan - Siregar, Boby Angurah; Nur Siagian, Muhammad Taufiqurrahman; Ulya, Basyarul (MODELING: Jurnal Program Studi PGMI, 2024)
This research examines the role of the Irsyadul Islamiyah Tanjung Medan Islamic Boarding School in preserving the Al-Barzanji tradition. Research Using descriptive qualitative research methods with data collection techniques through observation, interviews and documentation, this research aims to determine the Islamic boarding school's efforts to maintain and teach the Al-Barzanji tradition, identify the challenges faced, and reveal the benefits and socio-religious impacts. The research results show that Islamic boarding schools play an active role in preserving Al-Barzanji through routine learning, competitions, and community involvement in various religious activities. Supporting factors for preservation include the active role of Islamic boarding school caregivers, community support, and the availability of learning resources. Meanwhile, inhibiting factors include the decline in interest of students, lack of in-depth understanding of the meaning of Al-Barzanji, the influence of globalization, and the challenges of regeneration. The impact of preserving this tradition can be seen in increasing the spirituality of students, strengthening their character, and creating social harmonization between the Islamic boarding school and the surrounding community. This research concludes that the preservation of Al-Barzanji in Islamic boarding schools not only functions as a means of religious education, but also as a medium for maintaining the continuity of the Islamic cultural heritage of the archipelago. Abstrak Penelitian ini mengkaji peran Pondok Pesantren Irsyadul Islamiyah Tanjung Medan dalam melestarikan tradisi Al-Barzanji. Penelitian Menggunakan metode penelitian deskriptif kualitatif dengan teknik pengumpulan data melalui observasi, wawancara, dan dokumentasi, penelitian ini bertujuan untuk mengetahui upaya pesantren dalam menjaga dan mengajarkan tradisi Al-Barzanji, mengidentifikasi tantangan yang dihadapi, serta mengungkap manfaat dan dampak sosial keagamaannya. Hasil penelitian menunjukkan bahwa pesantren berperan aktif dalam melestarikan Al-Barzanji melalui pembelajaran rutin, perlombaan, dan pelibatan masyarakat dalam berbagai kegiatan keagamaan. Faktor pendukung pelestarian meliputi peran aktif pengasuh pesantren, dukungan masyarakat, dan ketersediaan sumber daya pembelajaran. Sementara faktor penghambat mencakup menurunnya minat santri, kurangnya pemahaman mendalam terhadap makna Al-Barzanji, pengaruh globalisasi, dan tantangan regenerasi. Dampak pelestarian tradisi ini terlihat pada peningkatan spiritualitas santri, penguatan karakter, serta terciptanya harmonisasi sosial antara pesantren dan masyarakat sekitar. Penelitian ini menyimpulkan bahwa pelestarian Al-Barzanji di pesantren tidak hanya berfungsi sebagai sarana pendidikan keagamaan, tetapi juga sebagai medium untuk menjaga keberlangsungan warisan budaya Islam Nusantara.